Systematic Literature Review: Empowerment Leadership on Performance - Darma Indragiri (Institute of Computer Science (IOCS), 2022)
One of the factors related to performance is leadership style, which in this study is about empowering leadership. The role of empowering leadership is about how to make an employee become independent and able to lead himself. The purpose of this study was to review systematically the existing research on empowering leadership and its relation to performance. This study is a systematic literature review (SLR) using a research protocol, namely the preferred reporting items for systematic reviews and meta-analyses (PRISMA). This study traced all research related to empowering leadership from 2012 to 2022. In total, 7 of the 39 studies found at Scopus were included in the review. Researchers used The Joanna Briggs Institute (JBI) Critical Appraisal to analyze the quality of the methodology. The findings obtained that empowerment leadership can affect performance and mediated by several factors such as self-efficacy for self-motivation, increasing meaningfulness in the team, seeking feedback behavior, orientation to a need, or through traditional things. The limitation/implication of this research is that scientific publications based on only one database, namely Scopus. This study also offers opportunities for further empirical research, both related to methods, factors that mediate and moderate empowerment leadership related to improving performance.